Plan Parcial Como Estrategia de Intervención Urbana Para Mejorar el Espacio Público de Rivera Huila (2024)
The municipality of Rivera, in Huila, faces a severe shortage of public space in its central area, exacerbating congestion during weekends. This situation stems from the influx of local rural population and visitors from the city of Neiva. The high demand for goods and services cannot be adequately met due to insufficient space for street vendors, impacting their competitiveness, quality of life, and the local economy. The lack of adequate public space in Rivera not only affects the quality of life for residents and traders but also hampers the local economy and market competitiveness. It is crucial to develop a plan that enhances public space and relocates vendors to larger, organized areas, benefiting the entire community and positively impacting the local economy.